(untitled) (Bangladesh Journal of Botany, 2008)
A field experiment was conducted in Amasya conditions in northern Turkey for two years in order to determine the effect of zinc and molybdenum fertilization on chickpea following a completely randomized block design with three replications. Doses of zinc (Zn0 : 0, Zn1 : 1 ppm, Zn2 : 2 ppm) and molybdenum (Mo0 : 0, Mo1 : 0.05 ppm, Mo2 : 0.1 ppm) were applied on leaf when the plants were in vegetative stage. Variation of years on all investigated characters was statistically significant. Applied zinc or molybdenum failed to show any significant effect on any parameter. It was found that effect of Zn Ã Mo interaction was statistically significant (p < 0.01) on the seed yield. The highest seed yield resulted from Zn2 (2 ppm) Ã Mo0 interaction. This was followed by Zn1 (1 ppm) Ã Mo1 (0.05 ppm) and Zn1 Ã Mo2 doses showing no statistical differences from each other. Â Key words: Chickpea, Seed yield, Zinc, Molybdenum, Response DOI = 10.3329/bjb.v36i2.1503 Bangladesh J. Bot. 36(2): 145-149, 2007 (December)